Modular Learning and Educational Inequality in Rural Philippine Secondary Education - Aldrin Boocan (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
This study investigates modular learning, defined as self-paced, independent study using learning modules, as a dimension of educational inequality in rural Philippine secondary Education. It focuses on how students navigate learning amid limited instructional support, including direct guidance, feedback, and teaching interaction, as well as uneven access to resources. A qualitative descriptive design was employed. Data were collected through in-depth, face-to-face interviews with ten Grade 11 students at a geographically isolated public secondary school. Thematic analysis using QualCoder 3.8 identified patterns in learning strategies, instructional conditions, and affective responses. Students developed adaptive learning strategies, including repeated reading to reinforce understanding, incremental problem-solving by breaking complex problems into manageable steps, and selective help-seeking when necessary. These strategies partially compensated for reduced teacher mediation. Their effectiveness depended on instructional clarity, the availability and responsiveness of support, and students’ affective states. Autonomy served as a conditional resource, providing flexibility but also increasing cognitive and emotional demands. Academic performance resulted from the interaction among learning strategies, instructional conditions, and affective responses, leading to uneven outcomes within the same modular system. This study is limited by its small sample size, single rural context, and reliance on self-reported data. Future research should examine the proposed interactional framework across diverse settings and assess interventions that enhance instructional support in modular learning environments. This study reframes modular learning as an equity-related issue, challenging learning-style explanations and proposing an interactional framework. In this framework, learning outcomes result from the dynamic interplay among strategy, context, and affect. The study provides a context-sensitive perspective for designing more equitable and sustainable modular learning systems in rural settings.